Pelatihan Menulis Puisi dengan Memanfaatkan Diksi Lokal di SMP Negeri 2 Pulau-Pulau Babar Kabupaten Maluku Barat Daya - Lewier, Mariana; Rutumalessy, Merlyn (Universitas Pattimura, 2024)
Alignment with the literacy movement and literary appreciation in the 21st century is very important in language and literature learning because it is one of the aspects that determines the quality and quality of education. So, it is necessary to make various continuous efforts that lead to adequate standards of success. The reality encountered in Maluku Province shows that learning in schools today has not been able to realize expectations for the achievement of student competence in literacy and literary creation properly and evenly. This can also be seen in the reality at SMP Negeri 2 Pulau-Pau Babar, East Babar Sub-district, Southwest Maluku Regency. The demands of 21st-century skills must be mastered, but which schools have not been able to foster literacy and appreciation of the Indonesian language and literature among teachers and students. This is the main basis for the implementation of this community service activity. The expected target is the students of SMP Negeri 2 Pulau-Pau Babar who still have a local language, namely the Southeast Babar language, who can develop literary potential combined with the creativity of processing local language vocabulary. This activity is directed at poetry writing training that utilizes local diction as an application of the multiliteracy learning model. The results show that students generally do not master local diction, so that only a few words are used in their poetry creation.